Study on Exorcism in Mark’s Gospel: Implications of Jesus’ Perspective for Today - Olusola Igbari (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
Exorcism is a theological term which has engaged the minds of some New Testament Scholars in recent times at least in last three decades. It is a universal phenomenon. Research has discovered that some churches especially orthodox ones have not paid much cognizance to this aspect of Jesus’ ministry. This study is an attempt to investigate what exorcism is and how is this ministry being addressed by the contemporary church using St. Mark’s narratives as the framework. Humans daily demands for a paradigm shift by the church to also engage in deliverance ministry instead of the focus on “prosperity message.” The Church should be aware that prosperity message can not have desired effect until lives of humans enjoy maximal health that can make life worthy living. Jesus in St. Mark’s Gospel showed examples of how and what the Church of God should address on the presence of evil spirits or demonic forces in the world of evil that is ravaging the lives of many within God’s creation. This chapter tried to identify salient areas of concern in addressing the issue of exorcism especially in the 21st Century Church. The last hope of the common man is the church. The reality of the existence of evil spirits and demonic forces which cannot be contended. If human person needs to achieve his destiny in life according to God’s purpose, then issues that can hinder the fulfilment of that destiny should be keenly addressed by individuals or the church to whom the gift of exorcism is deposited.